The influence of ethical attitudes and purchase behaviour for pirated software - Phau, Ian (School of Marketing, Curtin Business School, 2010)
This study investigates the ethical attitudes and purchase behaviour of Indonesian consumers towards software piracy. While previous studies have uncovered various motivations that drive consumers from different countries to engage in this undesirable behaviour, changes in the business landscape, including advancement in technology, necessitates a revisit into the attitudes and purchase intentions towards pirated software. It is found that habitual behaviour, integrity, facilitating conditions, and personal gratification are significant predictors of consumers' attitudes towards software piracy. Habitual behaviour and facilitating conditions are also found to be predictors of purchase intention. In contrast to prior studies, collectivism, normative and informative susceptibility, and value consciousness do not influence either attitudes towards and purchase intentions of pirated software. The main implication of this study is the clear indication that different strategies need to be formulated to curb software piracy in an emerging economy such as Indonesia.